Answer:
no
Step-by-step explanation:
this is because when dealing with the power, it involves multiplication
19 x 4 is the equation and the answers is 76
Answer:
Step By Step Explanation:
Apply Rule - (-a) = a
Multiply: 4 · 6 = 24
Expand
=
Simplify
=
━ Mordancy ━
The greatest common factor will be (x² – xy + y²).
<h3>Greatest common factor</h3>
This is a value or expression that can divide the given expressions without leaving a remainder.
Given the following expressions
x^3+^3 and x^2 - xy + y^2
Expand x^3+y^3
x^3+y^3 =(x + y)(x² – xy + y²).
Since (x² – xy + y²) is common to both expression, hence the greatest common factor will be (x² – xy + y²).
Learn more on GCF here: brainly.com/question/902408
#SPJ1